Preparation and properties of a fast‐cross‐linking α‐cyanoacryloyloxyethyloxypropyl‐functionalized polydimethylsiloxane. Issue 12 (8th September 2022) - Liu, Qingyue; Dong, Hong; Guo, Shiping; Zhang, Yipin; Wang, Erlei; Qu, Zhirong; Chen, Daowei; Huang, Liangbing; Hou, Jianchao; Zheng, Yunfeng; Wu, Chuan
Abstract: α‐cyanoacryloyloxyethyloxypropyl‐functionalized polysiloxanes were prepared using a condensation reaction between the adduct of anthracene/α‐cyanoacryloyl chloride and hydroxyethyloxypropyl‐modified polydimethylsiloxanes, followed by a retro‐Diels–Alder reaction to deprotect the anthracene. Structures of the obtained polymers and their intermediates were characterized using 1 H NMR, 13 C NMR, and FT‐IR spectroscopies. Under mild conditions such as at room temperature with a relative humidity of 60%, the α‐cyanoacryloyloxyethyloxypropyl‐functionalized polysiloxanes could be completely cured within 3 minutes. With a small amount of N, N ‐dimethyl‐ p ‐toluidine as the initiator, the curing time could be further shortened to 3–5 seconds. Various factors affected on the cross‐linking density and the average molecular weight between two adjacent cross‐linking points were investigated. The results indicated that with the introduction of the α‐cyanoacryloyloxyethyloxypropyl group, α‐cyanoacryloyloxyethyloxypropyl‐functionalized PDMS exhibited much better thermal stabilities than that of pure poly(ethyl α‐cyanoacrylate). Besides, the introduction of an α‐cyanoacryloyloxyethyloxypropyl group in the PDMS molecule also eliminated the crystallization behavior and glass transition temperature of PDMS. The results of the water contact angle test showed the interfacial characteristics of the prepared material changed significantly relative to pure PDMS. With the increase in the content of the functional group, the water contact angle of the material showed an overall increasing trend. Abstract : The α‐cyanoacryloyloxyethyloxypropyl‐functionalized polysiloxanes could be completely cured within 3 minutes under mild conditions, and with a small amount of N, N ‐dimethyl‐ p ‐toluidine as the initiator, the curing time could be further shortened to 3–5 seconds. The introduction of α‐cyanoacryloyloxyethyloxypropyl group changed the water contact angle of silicone rubber and extended their working temperature range.